1989
DOI: 10.1084/jem.170.5.1635
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage colony-stimulating factor (rM-CSF) stimulates pinocytosis in bone marrow-derived macrophages.

Abstract: Incubation of murine bone marrow-derived macrophages (BMM) in medium containing recombinant macrophage colony-stimulating factor (rM-CSF) stimulated influx, efflux, and the net accumulation of the fluid-phase pinocytic marker, lucifer yellow (LY). Stimulation was dose dependent, occurred within 5 min of addition of the growth factor, and was sustained. Previous experiments had shown that BMM treated with PMA were stimulated to accumulate LY, but compared with rM-CSF-treated cells, the onset of stimulation in P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
171
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(179 citation statements)
references
References 29 publications
8
171
0
Order By: Relevance
“…These contrasting results could be explained considering that the mechanisms that regulate endocytosis might differ in different cells. Supporting this possibility it has been described that, not only the routes for macropinocytosed Ags, but also the sensitivity of macropinocytosis to microtubule and microfilament destabilizing drugs differ between professional phagocytes and other cell types (38,59,(61)(62)(63). However, our observations made in bicarbonate-free medium support that, as observed in other cell types, acidification of cytosol exerts an inhibitory effect on DC endocytosis.…”
Section: Discussionsupporting
confidence: 89%
“…These contrasting results could be explained considering that the mechanisms that regulate endocytosis might differ in different cells. Supporting this possibility it has been described that, not only the routes for macropinocytosed Ags, but also the sensitivity of macropinocytosis to microtubule and microfilament destabilizing drugs differ between professional phagocytes and other cell types (38,59,(61)(62)(63). However, our observations made in bicarbonate-free medium support that, as observed in other cell types, acidification of cytosol exerts an inhibitory effect on DC endocytosis.…”
Section: Discussionsupporting
confidence: 89%
“…The BMMf were derived by culturing BM cells in complete DMEM containing 2 mM glutamine, 50 U/mL penicillin, 50 mg/mL streptomycin, 10% FCS (Gibco, Gaithersburg, MD, USA) and 1 ng/mL recombinant macrophage colony stimulating factor (Peprotech, Rocky Hill, NJ, USA). BMDC were derived by culturing in complete RPMI 1640 supplemented with 1 ng/mL recombinant granulocyte/monocyte-colony-stimulating factor and 1 ng/mL rIL-4 (Peprotech), as described previously [59,60]. Differentiation to DC and Mf was assessed by morphologic observation and detection of specific surface markers by FCM.…”
Section: Generation Of Bmdc and Bmm/mentioning
confidence: 99%
“…Macropinosomes are large vacuoles formed as a result of massive uptake of the extracellular fluid. Macropinosomes can be induced by cell activation with macrophage colony-stimulating factor (MCS-F) or phorbol myristate (Racoosin and Swanson, 1989), or during S. typhimurium invasion of phagocytic and non-phagocytic cells (Alpuche-Aranda et al, 1994;Garcia-del Portillo and Finlay, 1994a). The recent study of Racoosin and Swanson (1993) has shown that fusion of macropinosomes with lgpcontaining compartments in macrophages is initiated as early as 4 min after macropinosome formation.…”
Section: Discussionmentioning
confidence: 99%